Barriers to cervical cancer screening among women in Rivers East Senatorial District, Rivers State, Nigeria - Ekenedo, Golda Obiageri; Akagbuo, Rose Ngikanni; Elechi, Comfort Emma (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study investigated the barriers to cervical cancer screening among women in the Rivers East Senatorial District. The descriptive research design was adopted with a population consisting of 3,762,393 women in the Rivers East Senatorial District. A sample size of 880 was selected using a multi-staged sampling procedure. The instrument for data collection is a self-structured questionnaire titled “Barriers to Cervical Cancer Screening Questionnaire (BCCSQ)” with a reliability coefficient of 0.73. Data collected were coded and analyzed with the aid of the Statistical Product for Service Solution (SPSS) version 23.0 and analyzed using percentage and Chi-square at the 0.05 alpha level. The result of the study showed that, to a high extent, the factors that constituted barriers to cervical cancer screening among the women were non-affordability of the test (88.7%), fear of having a positive result (63.3%), and pain or fear of the process (59.4%). The tested hypotheses revealed that the variables that were significant barriers to cervical cancer screening were: fear of having a positive result ( X2 = 0.44, df = 1, p = 0.00), and pains or fear of the process ( X2 = 15.69, df = 1, p = 0.00). It was concluded that the barriers to cervical cancer screening were fear of having positive results and pain or fear of the process. It was recommended, among others, that the government closely monitor the delivery of cervical cancer screening services through its state and local government supervisors to ensure that the services are rendered at no cost as stipulated by the government. This will help to curb the issue of non-affordability.